ANALISIS DESKRIPTIF SOSIAL MEDIA TWITTER DALAM PROSES PEMBENTUKAN OPINI KAMPANYE GUBERNUR JAWA BARAT 2018 DALAM 30 HARI PERTAMA - umam, ahmad hairul; perdana, kiki esa (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2019)
This study aims to analyze the process of opinion formation through twitter social media during the campaign period of Governor Election of West Java using qualitative method. Collection data in this study was based on observations of the @ridwankamil account for 30 days of the campaign period, from 15 February to 15 March 2018. The selection of accounts for one of the Governor Candidates of West Java was based on the subjectivity of the researchers' assessment through observations on social media. The researchers grouped 4 major issues into the theme in the process of forming a campaign opinion in the contents of the @ridwankamil account; Program Vision Vision, Religion, Performance Achievement, and Cultural Identity. The analysis during the 30-day campaign the first account @ridwankamil voiced a lot of vision, mission, programs noted as much as 60%, religion 16, 25%, 13.75% performance achievement and 10% cultural identity. Opinion of the campaign that is spread through Twitter is able to attract the attention of most of the people of West Java through direct responses from followers with various kinds of response. The formation of opinions through Twitter is one form of self-proof of modernization in a campaigning style. The @ridwankamil account is able to utilize Twitter social media as a way of forming and leading opinions by interacting with the public because it does not have mainstream media as a means of delivering messages. The responses obtained from followers are influenced by the ease of accessing Twitter social networks and the high interest of West Java residents who actively use Twitter social media